BIOANALYSIS METHOD DEVELOPMENT AND VALIDATION OF SMALL MOLECULES IN PHARMACEUTICAL INDUSTRY: A BIOANALYST REVIEW POINT - S, SATHESHKUMAR; V, MURUGANANTHAM; SABAPATHI S, KANAGA; A, CHITHRA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The focus of bioanalysis employed for the quantitative determination of an active analyte(s) and their metabolite(s) in the biological matrix such as plasma, serum, blood, cerebrospinal fluid, and tissues. The extraction of analyte and metabolite in the biological fluids is carried out using different separation methods such as protein precipitation, liquid-liquid extraction, and solid phase extraction. Bioanalytical method development and validation in the pharmaceutical industry are to provide an assessment and interpretation of pharmacokinetics, pharmacodynamics, toxicokinetics, bioavailability/bioequivalence, and therapeutic drug monitoring relationships. This review paper aims to provide a simple and accurate scientific background to improve the quality for development and validation of a bioanalytical method for small molecules with industrial technique as per regulatory agency requirements (United States Food and Drug Administration, EMEA, International Council for Harmonisation and ANVISA).